The Use of Virtual Stream Mapping in Business Process Re-Engineering for Order Fulfillment Improvement at PT. X - Farrandi, Grant; Aritonang, Kinley (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2025)
MSMEs in the manufacturing sector often face challenges in the efficiency of the production process, especially when implementing a make-to-order system that leads to high product variety and long lead times. This research aims to design improvements in the production process at PT. X, a furniture MSME in Bandung, by applying the Value Stream Mapping (VSM) and Business Process Re-engineering (BPR) methods. VSM is used to map initial conditions and identify non-value-added activities (waste), while BPR is used to formulate radical remedial solutions. The results of the analysis showed several main problems, namely delays in the supply of raw materials, the absence of standardization of sofa frames and covers, and production processes that ran in parallel. The proposed solutions include the implementation of make-to-stock and make-to-order hybrid systems, the implementation of safety stock of frame materials, and the standardization of dimensions and processes. These changes result in more efficient production processes, shorten order fulfillment times, and improve product quality consistency. This research shows that the integration of VSM and BPR can be a strategic approach in improving the manufacturing performance of MSMEs.